Successful endoscopic sclerotherapy with bile duct stenting for a vascular malformation neighboring the duodenal papilla in blue rubber bleb nevus syndrome. Issue 1 (10th April 2022) - Unoura, Shingo; Toya, Yosuke; Kasugai, Satoshi; Kumei, Tomo; Yamazato, Masanao; Sasaki, Yutaka; Eizuka, Makoto; Oizumi, Tomofumi; Morishita, Toshifumi; Tagane, Seiya; Shiohata, Takeshi; Yanai, Shunichi; et al.
Abstract: A 14‐year‐old girl, who had been diagnosed with blue rubber bleb nevus syndrome, was referred to our hospital because of iron deficiency anemia. Esophagogastroduodenoscopy revealed a dark and red‐colored vascular malformation occurring just above the duodenal papilla. Because the lesion was regarded as the cause of the anemia, we performed polidocanol injection therapy with bile duct stenting. Since esophagogastroduodenoscopy performed a month later revealed a scarred ulcer, the bile duct stent was removed. She has been under observation as an outpatient without any symptoms.